Trading up: An EU trade policy for better market access and resilient sourcing - Fredrik Erixon; Oscar Guinea; Philipp Lamprecht; Oscar du Roy; Elena Sisto; Renata Zilli (European Centre for International Political Economy (ECIPE), 2024)
Europe's competitiveness could be substantially improved by a trade policy that facilitates more trade and other forms of cross-border exchange. The evidence is clear: the EU trades less with the rest of the world than would be expected given the size of its economy. With 85 percent of global growth happening outside of the EU - and with an increasing share of all new technologies, innovations, patents, human capital, and R&D expenditure emerging in other parts of the world than Europe - the EU needs to find better ways to integrate with international markets. It is now becoming urgent for the EU to revive its international trade policy.
Keywords: 330